2016
DOI: 10.1159/000446181
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Antigen-Specific Immunoglobulin E Immunoassays against Ara h 2 and Ara h 8 Peanut Components in Child Food Allergy

Abstract: Background: Peanut allergy is one of the most severe food allergies in children. The diagnostic gold standard is the oral food challenge (OFC). However, OFC has inherent risks and is time consuming. The measurement of specific immunoglobulin E (sIgE) to peanut components in blood detects peanut sensitization, but the decision point predicting allergy is still unclear. The aim of this study was to determine the diagnostic value of these tests for the evaluation of child peanut allergy. Methods: In this retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 33 publications
3
47
0
1
Order By: Relevance
“…Using component-specific diagnosis, it was shown that allergic rhinitis to birch pollen in adolescence can be predicted by IgE reactivity to pathogenesis-related class 10 proteins in early childhood [181] and that sensitization to Fel d 1 and Can f 1 in childhood were associated with symptoms to cat and dog in adolescence [182]. Likewise, high Ara h 2 IgE titers were shown to be associated with peanut-induced anaphylaxis [183]. In the case of mite allergy, CRD with the MeDALL chip indicated that IgE responses to mites were initiated by Der p 1, Der p 2 or Der p 23 and increased in prevalence along the first decade of life [184].…”
Section: Clinical Pictures: Asthma Rhinitis/rhinosinusitis Atopic Dmentioning
confidence: 99%
“…Using component-specific diagnosis, it was shown that allergic rhinitis to birch pollen in adolescence can be predicted by IgE reactivity to pathogenesis-related class 10 proteins in early childhood [181] and that sensitization to Fel d 1 and Can f 1 in childhood were associated with symptoms to cat and dog in adolescence [182]. Likewise, high Ara h 2 IgE titers were shown to be associated with peanut-induced anaphylaxis [183]. In the case of mite allergy, CRD with the MeDALL chip indicated that IgE responses to mites were initiated by Der p 1, Der p 2 or Der p 23 and increased in prevalence along the first decade of life [184].…”
Section: Clinical Pictures: Asthma Rhinitis/rhinosinusitis Atopic Dmentioning
confidence: 99%
“…Therefore, it is of increasing importance to focus on potential marker allergens to understand the mechanistic processes. Currently, the storage protein Ara h 2 is acknowledged as the most relevant marker allergen, associated with severe, sometimes fatal reactions [9,10,11,12]. Likewise, Ara h 6 is considered to predict peanut allergy with similar accuracy as both proteins belong to the 2S albumins with 59% sequence homology [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It should be considered that OFC tests bear the risk of severe allergic reactions, for which a history of anaphylactic reactions and older age are considered risk factors [52]. Since serum IgE levels to Ara h 2 have both high negative and positive predictive values, the number of OFC needed in suspected peanut allergy can be reduced [53]. In peanut-allergic patients from China, Ara h 9, a nonspecific lipid transfer protein, was identified as a major allergen [54].…”
Section: Improving the Diagnosis And Treatment Of Food Allergymentioning
confidence: 99%